New African species of Helina Robineau-Desvoidy (Diptera, Muscidae) - Couri, Márcia; Pont, Adrian (Zootaxa, 2016)
The study of Afrotropical Muscidae deposited in the Natural History Museum (BMNH), London, United Kingdom, revealed four new species of Helina Robineau-Desvoidy, herein described and illustrated. Helina duocolorata sp. nov. is described from Kenya, Helina longicerca sp. nov. and Helina sexnotata sp. nov. from Nigeria, and Helina mediomaculata sp. nov. from Angola. All types are deposited in the collection of the BMNH. Some corrections are made to the entries under Helina in the Catalogue of the Diptera of the Afrotropical Region (Pont 1980).